(untitled) (Global Journal of Human-Social Science, 2025)
This research aims to analyze neologisms on the social media platforms X formerly Twitter and Facebook in Brazil focusing on the formation and use of loanwords in politically themed posts The theoretical framework is based on works by Alves 2004 2007 Biderman 1978 2001 Carvalho 2000 2006 Guilbert 1975 Sablayrolles 2019 among others The findings indicate that loanword neologisms often creatively adapted into Portuguese through morphological and semantic processes reflect speakers strategies to express criticism humor and political positioning within a highly polarized digital environment Most of these items display some degree of adaptation suggesting an active process of lexical appropriation for argumentative mocking or ironic purposes Their frequency during specific periods such as elections and health crises highlights the connection between neologisms and socio-political events in Brazil Ultimately this study underscores the dynamic role of social media in shaping contemporary lexical innovation and political expression